The importance of a carbon tax for timely and cost-effective decarbonisation-a case study from Cyprus - Sotiriou, Chryso; Zachariadis, Theodoros (My University, 2020)
In European countries greenhouse gas emissions abatement seems to be most challenging in those sectors of the economy which are not subject to the European Union’s Emissions Trading System. In this chapter we examine decarbonisation options for the EU Member State of Cyprus. We consider the adoption of abatement measures coupled with the implementation of a gradually increasing carbon tax. We combine a long-term energy forecast model with an optimisation model that examines least-cost abatement pathways for the medium-and the long-term objective. Our simulations provide evidence that the lack of ambition in the medium-term will lock the economy into a carbon-intensive trajectory. For this purpose, we find that a carbon tax in the order of 120 Euros per tonne of CO2 can facilitate a transition to a low-carbon economy. Taking into account environmental side-benefits of emission abatement, ambitious policies turn out to be the socially optimal approach.
Keywords: carbon tax; Low-carbon Future